The Transcriptional Co-factor IRF2BP2: A New Player in Tumor Development and Microenvironment - Pastor, Tatiane P.; Peixoto, Barbara C.; Viola, João P. B. (Frontiers in Cell and Developmental Biology, 2021)
Interferon regulatory factor 2-binding protein 2 (IRF2BP2) encodes a member of the IRF2BP family of transcriptional regulators, which includes IRF2BP1, IRF2BP2, and IRF2BPL (EAP1). IRF2BP2 was initially identified as a transcriptional corepressor that was dependent on Interferon regulatory factor-2 (IRF-2). The IRF2BP2 protein is found in different organisms and has been described as ubiquitously expressed in normal and tumor cells and tissues, indicating a possible role for this transcriptional cofactor in different cell signaling pathways. Recent data suggest the involvement of IRF2BP2 in the regulation of several cellular function, such as the cell cycle, cell death, angiogenesis, inflammation and immune response, thereby contributing to physiological cell homeostasis. However, an imbalance in IRF2BP2 function may be related to the pathophysiology of cancer. Some studies have shown the association of IRF2BP2 expression in hematopoietic and solid tumors through mechanisms based on gene fusion and point mutations in gene coding sequences, and although the biological functions of these types of hybrid and mutant proteins are not yet known, they are thought to be involved in an increase in the likelihood of tumor development. In this review, we address the possible involvement of IRF2BP2 in tumorigenesis through its regulation of important pathways involved in tumor development.